Chronic exposure to complex metal oxide nanoparticles elicits rapid resistance in Shewanella oneidensis MR-1. Issue 42 (9th September 2019) - Mitchell, Stephanie L.; Hudson-Smith, Natalie V.; Cahill, Meghan S.; Reynolds, Benjamin N.; Frand, Seth D.; Green, Curtis M.; Wang, Chenyu; Hang, Mimi N.; Hernandez, Rodrigo Tapia; Hamers, Robert J.; Feng, Z. Vivian; Haynes, Christy L.; et al.
Abstract : We provide the first evidence of permanent bacterial resistance following exposure to nanoparticles that were not intended as antibacterial agents. Abstract : Engineered nanoparticles are incorporated into numerous emerging technologies because of their unique physical and chemical properties. Many of these properties facilitate novel interactions, including both intentional and accidental effects on biological systems. Silver-containing particles are widely used as antimicrobial agents and recent evidence indicates that bacteria rapidly become resistant to these nanoparticles. Much less studied is the chronic exposure of bacteria to particles that were not designed to interact with microorganisms. For example, previous work has demonstrated that the lithium intercalated battery cathode nanosheet, nickel manganese cobalt oxide (NMC), is cytotoxic and causes a significant delay in growth of Shewanella oneidensis MR-1 upon acute exposure. Here, we report that S. oneidensis MR-1 rapidly adapts to chronic NMC exposure and is subsequently able to survive in much higher concentrations of these particles, providing the first evidence of permanent bacterial resistance following exposure to nanoparticles that were not intended as antibacterial agents. We also found that when NMC-adapted bacteria were subjected to only the metal ions released from this material, their specific growth rates were higher than when exposed to the nanoparticle. As such, we provide here the first demonstration of bacterial resistance to complex metal oxide nanoparticles with an adaptation mechanism that cannot be fully explained by multi-metal adaptation. Importantly, this adaptation persists even after the organism has been grown in pristine media for multiple generations, indicating that S. oneidensis MR-1 has developed permanent resistance to NMC.